The Place of the Legend of Alexander of Macedon in the Larger Context of the Old Romanian Literature - Dan-Tudor Ionescu (In Gremium. Studies in History, Culture and Politics, 2019)
The main aim of this quite short study was to complete the essential image of Alexander of Macedon as he appears through the pages of the Romanian Alexandria, with a an overview on the so called Old Romanian “popular” literature: somehow the true essence of this hero (Alexander of Macedon) and of his legend had eluded me many times. Compared with the Romanian History of Troy, so faithful still to Homer and his epigonoi, the Romanian Alexandria seems to the untrained reader of old Romanian literature (like the author of these lines confesses to be) a collection of wild fantasy stories. This article tries to highlight the place of this tale about Alexander the Great (his legendary story) in the larger context of the popular old Romanian literature and the stories of some of its manuscripts and early printed versions, stories which are sometimes even stranger than the tale of the main character of the legend, Alexander himself.